Isu Multikulturalisme Dalam Transisi Perubahan Dunia - Prawoto, Sigit (Studi Budaya Nusantara, 2021)
Multiculturalism is increasingly becoming an important discourse in the global community, that along with the increasing appearance of local identities and territorial claims. The rise of several candidates for national leaders in many countries and the winners of political contestations in those countries can be interpreted as a reaction to the ongoing multiculturalism problem. Observations made on political discourse in several European countries and Indonesia show that the issue of identity is facing multiculturalism today. The problems of conflicting identity claims that have been going on for years are accumulating and earn reinforcement when large waves of migration occur from other countries. The problems of multiculturalism in Indonesia as a residue of general election of 2014 are still clear to this day. The issue of identity continues to enliven public discourse until the jargons of nationalism and decisive action from the state emerge to compensate.